Mansfield park - Austen,Jane (DC, 2007)
A young girl named Fanny Price comes to live with her wealthy uncle and aunt, Sir Thomas and Lady Bertram. Fanny's family is quite poor; her mother, unlike her sister Lady Bertram, married beneath her, and Fanny's father, a sailor, is disabled and drinks heavily. Fanny is abused by her other aunt, Mrs. Norris, a busybody who runs things at Mansfield Park, the Bertrams' estate. The Bertram daughters, Maria and Julia, are shallow, rather cruel girls, intent on marrying well and being fashionable. The elder son, Tom, is a roustabout and a drunk. Fanny finds solace only in the friendship of the younger son, Edmund, who is planning to be a clergyman. Fanny grows up shy and deferential, caught as she typically is between members of the Bertram family.